Sociological Contributions to School Choice Policy and Politics Around the Globe: Introduction to the 2020 PEA Yearbook. Issue 1 (January 2020) - Potterton, Amanda U.; Edwards, D. Brent; Yoon, Ee-Seul; Powers, Jeanne M.
The introduction to the Yearbook provides an overview of the global context of school choice policies and practices, trends in research and reform, and extant knowledge about research on school choice that draw upon the sociology of education. The article also highlights the contributions of the papers included in the Yearbook. The co-editors explain how the studies engage, complement, and extend existing streams of literature by bringing together a collection of contemporary sociological studies from the United States and other countries that illuminate understudied aspects of school choice reform policies, practices, and politics from across the globe. The Yearbook aims to raise the international profile of sociological research on school choice, and document how school choice policies and programs can be understood through a sociological lens, with a focus on how stakeholders perceive, experience, and respond to these reforms in local settings. This Yearbook also offers directions for future studies.